2020
DOI: 10.1111/ajae.12136
|View full text |Cite
|
Sign up to set email alerts
|

Insured Loans and Credit Access: Evidence from a Randomized Field Experiment in Northern Ghana

Abstract: We conducted a two‐treatment randomized control trial in northern Ghana to investigate how bundling index insurance with agricultural loans affects smallholder access to credit. In one treatment, farmer groups were invited to apply for production loans bundled with an index insurance contract that, in the event of a drought, indemnifies farmers directly (micro‐insured loans). In the second treatment, farmer groups were invited to apply for production loans bundled with an index insurance contract that, in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 43 publications
0
21
1
Order By: Relevance
“…We find no additional positive effect of default‐income insurance. These results are surprising and conflict with Giné and Yang (2009), who find a negative impact of insurance on demand for credit, and other literature that finds no effect (Karlan et al., 2011; Mishra et al., 2019). We speculate that our experiment may be picking up an internal cost of default, a default aversion that may influence borrowing behavior but is difficult to detect in the randomized controlled trial framework employed elsewhere in the literature.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…We find no additional positive effect of default‐income insurance. These results are surprising and conflict with Giné and Yang (2009), who find a negative impact of insurance on demand for credit, and other literature that finds no effect (Karlan et al., 2011; Mishra et al., 2019). We speculate that our experiment may be picking up an internal cost of default, a default aversion that may influence borrowing behavior but is difficult to detect in the randomized controlled trial framework employed elsewhere in the literature.…”
Section: Discussioncontrasting
confidence: 79%
“…Karlan, Kutsoati, McMillan, and Udry (2011) and Mishra et al. (2019) find no impact of index insurance on credit demand, although Mishra et al. (2019) does find that when banks offer insured loans, farmers are more likely to obtain credit.…”
Section: Introductionmentioning
confidence: 99%
“…Still, the linking or bundling of credit with insurance is a topical issue at the present (Giné and Yang, 2009) because of the partial substitution of collateral for insurance (Shee and Turvey, 2012). For example, in a RCT in Ghana, Mishra et al. (2021) find that insured loans increase farmers' likelihood of receiving credit by between 15 and 21% points.…”
Section: Insurance Studies Related To Demand and Supplymentioning
confidence: 99%
“…Still, the linking or bundling of credit with insurance is a topical issue at the present (Gin e and Yang, 2009) because of the partial AFR 82,5 substitution of collateral for insurance (Shee and Turvey, 2012). For example, in a RCT in Ghana, Mishra et al (2021) find that insured loans increase farmers' likelihood of receiving credit by between 15 and 21% points. In a subexperiment to an RCT (see Ndegwa et al, 2020;Shee et al, 2021) conducted a DCE on both farmers and insurers in Kenya and found that while Kenyan farmers found bundling insurance a positive attribute of insurance, the insurance professionals viewed credit bundling as being either negative or not significant.…”
Section: Livestock Insurance In Rural Chinamentioning
confidence: 99%
“…These results have important policy implications. First, since learning by doing is important for continuity in adoption, policies should be in place to provide complimentary environments (e.g., insurance through safety net programs (Alem & Broussard, 2018) and through groups (Gallenstein, Mishra, Sam, & Miranda, 2019; Hill, Hoddinott, & Kumar, 2013; Mishra et al., 2020), and formal training (Takahashi et al., 2020) so that initial barriers to adoption are broken, especially for female‐headed households, making learning more effective for future periods. The reduction in learning gap can encourage stickiness to technology adoption in the later periods (Ma & Shi, 2015), boost the agricultural productivity (Abate et al., 2018; Khonje et al., 2018), and reduce malnutrition (Pan et al., 2018; Zeng et al., 2017) that is much needed in SSA.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%